Peningkatan Hasil Belajar Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti dengan Menggunakan Media Pembelajaran Aplikasi Canva.Com pada Siswa SMK Pancasila - Bella Putriana Dewi; Nur Hidayah; Taufiq Usman (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
This research is backgrounded by learning media which is a facility and infrastructure to support the implementation of learning activities, without learning media, education will not run well and will affect student learning outcomes, therefore researchers formulate their problems and aim to find out: 1. Student learning outcomes before using learning media applications canva.com. 2. Student learning outcomes after using canva.com application learning media. 3. Improving student learning outcomes after using the learning media of the canva.com application. The research was conducted at SMK Pancasila 06 Jatisrono Wonogiri in May 2022, the research method used was classroom action research, this research was carried out in two cycles, the instrument used was the Learning Implementation Plan (RPP), the data collection technique used observation, tests and documentation, the data obtained was then processed by knowing the value, mean, interval, category, and procentration, from this study it can be concluded that: 1. The implementation of learning Islamic Religious Education and Ethics class XI AKL 5 SMK Pancasila 06 Jatisrono Wonogiri before using application learning media canva.com is included in the sufficient category because the average score of 57.32 is at intervals of 52-61, with sufficient categories. 2. The implementation of learning Islamic Religious Education and Ethics class XI AKL 5 SMK Pancasila 06 Jatisrono Wonogiri after using the application learning media canva.com is included in the sufficient category because the average score of 77.67 is at intervals of 70-84, with sufficient categories. 3. Improving student learning outcomes and learning by using application learning media canva.com can meet success indicators. By applying learning media using canva.com application, it can bring positive changes in improving student learning outcomes.